Animal models of seizures and epilepsy - Löscher, Wolfgang (Henry Stewart Talks, 2011)
Diverse models available, Invaluable preclinical approach for discovery of new treatments for epilepsy, Specific models for pharmacoresistant seizures, Models for the discovery of epilepsy-preventing drugs